2021
DOI: 10.3390/biology10030208
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Concentration of IgG against the Spike Receptor-Binding Domain That Predicts the Viral Neutralizing Activity of Convalescent Plasma and Serum against SARS-CoV-2

Abstract: Several hundred millions of people have been diagnosed of coronavirus disease 2019 (COVID-19), causing millions of deaths and a high socioeconomic burden. SARS-CoV-2, the causative agent of COVID-19, induces both specific T- and B-cell responses, being antibodies against the virus detected a few days after infection. Passive immunization with hyperimmune plasma from convalescent patients has been proposed as a potentially useful treatment for COVID-19. Using an in-house quantitative ELISA test, we found that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 60 publications
2
16
0
1
Order By: Relevance
“…We showed that the Wantaï total Ig concentrations and neutralizing antibodies titers of a population of health care workers were correlated and that a high neutralizing antibodies titer protected against reinfection ( 29 ). This correlation between neutralizing antibodies and anti-RBD-IgG determined by ELISA has also been found by others ( 30 32 ). It could be used to screen plasma donors to optimize the use of convalescent plasma to protect against lower respiratory tract disease.…”
Section: Discussionsupporting
confidence: 87%
“…We showed that the Wantaï total Ig concentrations and neutralizing antibodies titers of a population of health care workers were correlated and that a high neutralizing antibodies titer protected against reinfection ( 29 ). This correlation between neutralizing antibodies and anti-RBD-IgG determined by ELISA has also been found by others ( 30 32 ). It could be used to screen plasma donors to optimize the use of convalescent plasma to protect against lower respiratory tract disease.…”
Section: Discussionsupporting
confidence: 87%
“…In the analyzed cohort, the antibody titer peaked between week 2 and 4, and it was maintained up to week 24, consistently with how observed in the non-pregnant population ( 29 , 30 ). Although the lower number of collected samples due to some discontinuity during the follow-up, the neutralization titer significantly correlated with the IgG antibody titer, which is expected but not granted ( 31 ). Additional results showed that, while SARS-CoV-2-specifi IgG were present in 50% only of the asymptomatic subjects, strong antibody response was elicited by infection in all mild-to-critical patients.…”
Section: Discussionmentioning
confidence: 83%
“…Likewise, we have selected for our study an in-house ELISA coated with the RBD antigen because better diagnostic measures were obtained in comparison to the remaining antigens in terms of specificity. Other techniques to characterize serological responses to SARS-CoV-2 include SARS-CoV-2 titration, microneutralization assays [19], Western blotting [20], immunoblotting assay [21], luciferase immuno-precipitation technique [22] or microsphere immunoassay [23]. ELISA has a number of benefits compared to the other immunoassay techniques, including that it is a simple procedure with a 96-well microplate format in which simultaneous analyses can be performed.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the development of multi-species ELISAs has a significant advantage; human samples could be used to perform validation parameters, as is the approach used for the WANTAI SARS-CoV-2 Ab ELISA. In this study, we have employed an ELISA previously developed in our lab based on the RBD human SARS-CoV-2 antigen that has been previously found to be useful in detecting neutralizing anti-SARS-CoV-2 antibodies in different hosts, including humans [19], cats [2], ferrets [3] and experimental mice (unpublished). Thus, the absence of positive results in sheep is unlikely to be due to the poor performance of this ELISA in detecting sheep-derived anti-SARS-CoV-2 antibodies.…”
Section: Discussionmentioning
confidence: 99%